X RADIATION DOSE MONITORING FOR ADOLESCENT AND ADULT PATIENTS IN SELECTED HEALTH CARE ENVIRONMENT RELATED PLACES - Riandi, Kevin (UI Scholars Hub, 2021)
A study on patient absorption dose according to age group was carried out. The amount of absorbed A study on patient absorption dose according to age group was carried out. The amount of absorbed dose of X-ray radiation affect the body cells. Health care hospitals such as clinics, environments that use ionizing radiation. Based on the procedure for using ionizing radiation for medical purposes, the Indonesian Nuclear Energy Supervisory Agency recommends monitoring radiation doses for health workers on health service environment. Likewise with the patient, because the patient is directly exposed to the ionizing radiation. Some researh explained that the probability of the greatest stochastic effect on interventional cardiology procedures with X-rays of young patients whose radiation dose has been measured is the occurrence of leukemia, in other research found on baby and toddler patient that there was a significant difference in the absorbed dose in each patient's age group. This study aims to determine the comparison of the absorbed X-ray doses on thorax examination received by patients in the three youngest and oldest age groups. The data that support the calculation of the absorbed dose first find the exposure dose calculation by set value on the control panel of the X-ray machine to each patient is checked are the voltage, current, focal length of the patient's X-ray field, and the age of the patient. Determination of the absorbed dose was carried out using an equation, namely the milliroentgen unit. The exposure dose, milliRoentgen, was converted to an absorbable dose unit, mGy. Average absorption dose per age was compared by one-way ANOVA statistical analysis. The results showed that the absorbed dose of X-rays of patients at the Quantum Diagnostic Clinic for each age group had an insignificant comparison value. The absorbed dose in late adolescence and early adulthood did not have a significant difference. Dosage between early adolescence and late adulthood also did not have a significant difference. Thus, at the Denpasar Quantum Clinic, the absorbed dose of radiation received on young patients is relatively safe compared to the older age group. There was no significant difference in the value of the absorbed dose between one age group and another.